Understanding user experience of news applications by Taxonomy of Experience (ToE). Issue 11 (2nd November 2017) - Wang, Wen-Chia
ABSTRACT: Mobile phone is a necessary gadget for modern people nowadays. More and more users consume news and media content from smartphones via news applications or social media platform. It is important for news portals to understand young generation deeply to provide suitable service. This study introduces the method of taxonomy of experience (ToE) and its analytic approach of SEEing to understand college students' user experience of Taiwanese news applications on smartphones. Users were encouraged to express their feelings, opinions, and operation processes during the testing via the approach of 'think aloud'. The analytic approach of SEEing includes nine steps to categorise and analyse users' verbal commentary. More importantly, user experience is analysed via clear missions of each steps. A total of 80 participants were invited to evaluate four news applications that were developed by media in Taiwan. Each news application was evaluated by 20 participants. The outcomes show that the users' experience of news applications include the expectation of quick understanding, sharing, consistency, fun, importance, diversity, interests, and a wide range of topics. The outcome of this study provides an alternative way for news providers in Taiwan to re-evaluate what the users' real desires of news applications are.